Stock Dividends, Stock Splits, and Signaling. - Dravid, Ajay; Mcnichols, Maureen (Journal of Finance, 1990)
This paper provides evidence that firms signal their private information about future earnings by their choice of split factor. Split factors are increasing in earnings forecast errors, after controlling for differences in pre-split price and firm size. Further more, price changes at stock dividend and split announcements are significantly correlated with split factors, holding other factors constant, and with earnings forecast errors. These correlations suggest that management's choice of split factor signals private information about future earnings and that investors revise their beliefs about firm value accordingly. The analysis also suggests, however, that announcement returns are significantly correlated with split factors after controlling for earnings forecast errors. This suggests that earnings forecast errors measure management's private information about future earnings with error, that split factors signal other valuation-relevant attributes, or that a signaling explanation is incomplete.